(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This research explores the significance of women’s entrepreneurship in enhancing social welfare and driving economic development. Female entrepreneurs play a crucial role in generating employment, fostering innovation, boosting market competitiveness, and ensuring economic stability, all while advancing gender equality and improving social conditions. The study focuses on the influence of digitalization on women’s entrepreneurial ventures, especially in developing nations such as Uzbekistan. Although government initiatives aim to support women-led businesses, digital technologies have yet to make a substantial impact on their entrepreneurial activities. The findings emphasize that encouraging innovative enterprises owned by women can contribute to sustainable economic growth and social advancement.